(untitled) (International Journal of Chemical and Process Engineering Research, 2025)
Carbon dioxide removal from the atmosphere has emerged as one of the most critical strategies in responding to the accelerating climate crisis. It is important to develop rigorous and beneficial strategies and take steps to remove carbon dioxide from the atmosphere. In this study, bifurcation analysis and multi-objective nonlinear model predictive control are performed on a carbon dioxide removal model. Bifurcation analysis is a powerful mathematical tool used to address the nonlinear dynamics of various processes. Several factors must be considered, and multiple objectives must be met simultaneously. The MATLAB program MATCONT was used to perform the bifurcation analysis. The MNLMPC calculations were conducted using the optimization language PYOMO in conjunction with state-of-the-art global optimization solvers IPOPT and BARON. The bifurcation analysis revealed the existence of limit points. The MNLMPC converged to the Utopia solution. The limit points, which cause multiple steady-state solutions from a singular point, are highly beneficial because they enable the multi-objective nonlinear model predictive control calculations to converge to the Utopia point, representing the best possible solution in the model.